Chromoblastomycosis: A rare fungal infection from a nonendemic region—Southern Odisha - Akash Panigrahi; Sanghamitra Padhi; Indrani Mohanty (Journal of Dr. NTR University of Health Sciences, 2020)
Chromoblastomycosis, a slowly progressing localized fungal infection confined to the skin and subcutaneous tissue, is caused by dematiaceous fungi. Dermal lesions are pleomorphic and can range from small nodules to large papillary like eruptions. Herein, we report a case of chromoblastomycosis in a 26-year-old male caused by Fonsecaea pedrosoi. The patient was immunocompetent and had thorn injury 4 years back and developed a nonhealing ulcer on the medial aspect of his right leg, which was clinically suspected as tuberculous or carcinomatous lesion. Punch biopsy was done and sent in normal saline for the histopathological examination. Microscopically, sclerotic bodies, characteristic of chromoblastomycosis, were noticed on hematoxylin and eosin stained sections. Potassium hydroxide mount of the punch biopsy also revealed dematiaceous branching septate fungal hyphae. The fungal culture produced typical black colonies of Fonsecaea pedrosoi. The case is of interest because to the best of our knowledge it has so far not been reported from our region—southern part of Odisha.